A problem of packing of homothetic convex polytopes - Stoyan, Yu.G.; Chugay, A.M. (Reports of the National Academy of Sciences of Ukraine, 2017)
On the ground of an Φ-function for two convex polytopes, a mathematical model of the problem of packing of homothetic convex polytopes into a cuboid of a minimum volume is constructed. A number of characteristics of the mathematical model are pointed out. Based on the characteristics, a way of construction of starting points, a rapid algorithm of searching for local minima, and an original approach to the directed non-exhaustive search for local extrema to obtain a good approximation to a global extremum are offered. Numerical results are given.